Understanding How Local Wisdom Shapes Social Skills: A Microethnographic Study in Indonesian Elementary Classrooms - Ari Yanto; Sapriya; Enok Maryani; Mubiar Agustin (International Conference on Elementary Education, 2025)
This study aims to understand how Indonesian local wisdom values, such as gotong royong (cooperation), musyawarah (shared decision-making), and tepa selira (empathy), shape the social skills of elementary school students through daily learning practices. The study was conducted in three public elementary schools in Cirebon Regency, West Java, involving 21 students and 4 teachers as participants. Using a microethnographic approach, this study examined the social dynamics, discourse patterns, and participation structures that mediate social interactions in the classroom. Data were collected over eight weeks through classroom observations, video recordings, and semi-structured interviews with teachers and students. The analysis shows that local wisdom values function as cultural tools that strengthen empathy, social responsibility, and prosocial communication among students. Teachers play a crucial role in internalizing these cultural values through contextual pedagogical strategies that foster social awareness and collaboration. These findings contribute to the global discourse on culture-based social pedagogy by demonstrating how the integration of local values can enrich the social-emotional learning approach in multicultural elementary education contexts.